2015
DOI: 10.1021/mp5008212
|View full text |Cite
|
Sign up to set email alerts
|

CD33-Targeted Lipid Nanoparticles (aCD33LNs) for Therapeutic Delivery of GTI-2040 to Acute Myelogenous Leukemia

Abstract: CD33-targeted lipid nanoparticles (aCD33LNs) were synthesized for delivery of GTI-2040, an antisense oligonucleotide (ASO) against the R2 subunit of ribonucleotide reductase, to acute myelogenous leukemia (AML). These LNs incorporated a deoxycholate-polyethylenimine (DOC-PEI) conjugate, which has shown significant activity to facilitate oligonucleotide delivery. Anti-CD33 scFv (aCD33) was added as a targeting ligand. The delivery efficiency of this system was investigated both in vitro and in vivo. When cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Furthermore, PLGA-antiCD44-PTL nanoparticles inhibited the Kasumi-1 leukemic cells by decreasing its viability by 40% [ 47 ]. In addition, Li et al [ 48 ] reported that CD33-targeted lipid nanoparticles (aCD33LNs) they synthesized effectively delivered GTI-2040 to the intended target to inhibit the proliferation of Kasumi-1 cells. The effect of the nanoparticles (aCD33LN/GTI-2040) was 15-fold more effective than the known antileukemic drug, Ara-C.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PLGA-antiCD44-PTL nanoparticles inhibited the Kasumi-1 leukemic cells by decreasing its viability by 40% [ 47 ]. In addition, Li et al [ 48 ] reported that CD33-targeted lipid nanoparticles (aCD33LNs) they synthesized effectively delivered GTI-2040 to the intended target to inhibit the proliferation of Kasumi-1 cells. The effect of the nanoparticles (aCD33LN/GTI-2040) was 15-fold more effective than the known antileukemic drug, Ara-C.…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes were also developed to encapsulate GTI-2040 (also known as LOR-2040) and to target ribonucleotide reductase, which is overexpressed in cytarabine-resistant AML cells [71]. GTI-2040, targeting the R2 ribonucleotide reductase subunit, was evaluated in a Phase 1 clinical trial in combination with cytarabine.…”
Section: Liposomesmentioning
confidence: 99%
“…R2 downregulation was observed but no complete remission was noted, indicating that the effect of GTI-2040 needed to be enhanced [72]. GTI-2040-loaded immunoliposomes, grafted with an anti-CD33 to target AML cells, were designed and evaluated by Li et al [71]. These liposomes were previously formulated using an emulsion comprising lipids (2,3-dioleyloxy-propyltrimethylammonium chloride, dioleoylphosphatidylethanolamine, α-tocopheryl PEG-1000 succinate, and cholesterol) solubilized in ethanol and then injected in an HEPES buffer.…”
Section: Liposomesmentioning
confidence: 99%
“…Additionally, study conducted on mice model presented that nanoparticles-mediated delivery of ataxia-telangiectasia-mutated ( ATM ; radiosensitization gene) ASOs provide a way to sensitize of head and neck squamous-cell carcinoma cells to irradiation [ 87 ]. The newest studies presented by Li et al confirmed great potential of these agents in the treatment of acute myelogenous leukemia [ 88 ]. However, a better understanding of uptake mechanism of ASOs is crucial for development of anti-RNAs as effective antineoplatic compounds.…”
Section: Employment Of Nanomaterials For Delivery Of Nucleic Acid-basmentioning
confidence: 99%